PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PADA PT WIJAYA KARYA (PERSERO) TBK PERIODE 2012 – 2021 - Khadafi, Mouamar; Jamaluddin (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of the Return On Asset ratio and Debt to Equity Ratio on share prices at PT. Wijaya Karya, Tbk, both partially and simultaneously within a period of 10 years, namely from 2012 to 2021. The method used in this research is a quantitative descriptive method because this research is related to the research object, namely companies within a certain period of time by collecting data and information related to the company and adjusted to the research objectives. The data used is secondary data in the form of the balance sheet and profit and loss report of PT. Wijaya Karya, Tbk for the period 2012 – 2021 obtained through the Indonesian Stock Exchange (BEI). The analytical methods used are classical assumption test analysis, multiple linear regression analysis, coefficient of determination, and hypothesis testing. Based on the partial t test analysis, the calculated t result for Return On Assets was tcount 1,384 < ttable 1.943 with a significant value of 0.209 < 0.05, which means there is no partially significant influence on share prices. For the results of the t count, the Debt to Equity Ratio is t count -0,778 < t table 1.943 with a significant value of 0.462 > 0.05, which means that there is no partially significant influence on share prices. Then for the simultaneous F test analysis the results obtained are F count 1,732 > F table 4, 35 with a Sig value of 0.245 > 0.05, which means there is no significant simultaneous influence between Return On Assets and Debt to Equity Ratio on Stock Prices. Based on the test results, the coefficient of determination (R Square) is 0.331 or 33,1%. This shows that Return On Assets and Debt to Equity Ratio contribute 33,1% to the share price at PT. Wijaya Karya, Tbk during the period 2012 – 2021. Meanwhile, the remaining 66,9% ​​is influenced by other variables not used in this research.